Accurate and Sensitive Analytical Method for the Determination of Cyclanilide in Cotton and Cosmetic Pads at Trace Levels Using the Combination of Vortex Assisted Iron(II,III)/Reduced Graphene Oxide Nanocomposite Based Dispersive Solid Phase Extraction and High Performance Liquid Chromatography (HPLC) - Erarpat, Sezin; Maltepe, Esra; Er, Elif Ozturk; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2020)
A novel, accurate and sensitive analytical method was developed to determine cyclanilide using vortex assisted Fe3O4/reduced graphene oxide nanocomposite based dispersive solid phase extraction by high performance liquid chromatography (HPLC). An iron (II,III)/reduced graphene oxide nanocomposite (Fe3O4/rGO) was employed to extract and separate cyclanilide from aqueous solution. After the optimization of HPLC system, important parameters for the extraction method including mass of Fe3O4/rGO, pH, volume of buffer solution, nature/volume of eluent solution and vortex period were examined to obtain the highest extraction yields. Under the optimum conditions, the enhancement in the detection power was found to be 35-fold by the developed method. The limits of detection and quantification of the proposed method were 2.6 and 8.7 ng g(-1), respectively. In order to characterize the accuracy and applicability of developed method, recovery studies were performed upon cotton and cosmetic pads. High percent recovery results between 90 and 104% were obtained for cotton and cosmetic pad samples. Therefore; this method may be easily applied to cotton samples with excellent precision and accuracy.
Keywords: Cotton; cyclanilide; dispersive solid phase extraction; reduced graphene oxide nanocomposites; high-performance liquid chromatography (HPLC); SYNTHETIC COLORANTS; QUECHERS EXTRACTION; WATER; RESIDUES; MICROEXTRACTION; NANOPARTICLES; FABRICATION; FRUITS; Chemistry